Determination of Benzo(a)pyrene in Cigarettes Stubs by High Performance Liquid Chromatography - YAN, XIANGYANG; XIE, YUEQIN; FAN, HU; SHENG, LIANGQUAN; TONG, HONGWU; LIU, SHAOMIN (Asian Journal of Chemistry, 2010)
In present studies, a standard method for the quantitative determination of benzo(a)pyrene in cigarette stub has been developed. The analysis procedure involves a solid phase extraction after extracted with sonicator in cyclohexane. The determination with sensitive detection was attained by reversed-phase high-performance liquid chromatography with fluorescence detector. The detection limits of benzo(a)pyrene was 0.01 ng mL-1 at a signal/noise ratio of 3. The contents of benzo(a)pyrene in the stubs of several flue-cured cigarettes were 1-3 ng cig-1.